PENGARUH KEPEMILIKAN MANAJERIAL DAN KEPEMILIKAN INSTITUSIONAL TERHADAP KINERJA KEUANGAN PERUSAHAAN DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI: Studi Empiris Pada Perusahaan Manufaktur Sektor Industri Dasar Dan Kimia Yang Terdaftar Pada BEI - Wicaksono, Bagas; Fauzan, Fauzan (LP2M Universitas Bina Bangsa, 2025)
This study aims to analyze the influence of managerial ownership and institutional ownership on the company's financial performance with company size as a moderation variable in manufacturing companies in the basic and chemical industry sectors listed on the Indonesia Stock Exchange for the period 2018-2022. The sampling technique used purposive sampling, so that 114 samples were obtained that met the research criteria. The analysis method used is multiple linear regression analysis. The results of this study show that managerial ownership has an effect on the company's financial performance, while institutional ownership has no effect on the company's financial performance. Then the testing of moderation variables showed that the size of the company weakened the influence of managerial ownership and institutional ownership on the company's financial performance